2017
DOI: 10.1167/iovs.17-21445
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Suppresses a Cascade of Core Vicious Cycle in Dry Eye NOD Mouse Model: Involvement of Sphingosine-1-Phosphate Receptors in Infiltrating Leukocytes

Abstract: Leukocytes are involved in DED in the NOD mouse model. The therapeutic mechanisms of fingolimod may be associated with inhibitory roles of "cytokines-MMPs/MAPKs" cycle in NOD mouse ocular surface tissues by mediating S1PRs in infiltrating leukocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, they confirmed that complement played an essential role in inflammation of ocular surface. Xiao et al [33] stated that cytokines-MMPs/MAPKs vicious cycle played pivotal roles in the development of dry eye disease. Blockage or reversal of the cytokines-MMPs/MAPKs vicious cycle relieved inflammatory responses in ocular surface tissues and alleviated damage to goblet cells, lacrimal gland, cornea, conjunctiva, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they confirmed that complement played an essential role in inflammation of ocular surface. Xiao et al [33] stated that cytokines-MMPs/MAPKs vicious cycle played pivotal roles in the development of dry eye disease. Blockage or reversal of the cytokines-MMPs/MAPKs vicious cycle relieved inflammatory responses in ocular surface tissues and alleviated damage to goblet cells, lacrimal gland, cornea, conjunctiva, etc.…”
Section: Discussionmentioning
confidence: 99%